Estimates of the prevalence of speech and motor speech disorders in persons with complex neurodevelopmental disorders. - Shriberg, Lawrence D.; Strand, Edythe A.; Jakielski, Kathy J.; Mabie, Heather L. (Clinical Linguistics & Phonetics, 2019)
Estimates of the prevalence of speech and motor speech disorders in persons with complex neurodevelopmental disorders (CND) can inform research in the biobehavioural origins and treatment of CND. The goal of this research was to use measures and analytics in a diagnostic classification system to estimate the prevalence of speech and motor speech disorders in convenience samples of speakers with one of eight types of CND. Audio-recorded conversational speech samples from 346 participants with one of eight types of CND were obtained from a database of participants recruited for genetic and behavioural studies of speech sound disorders (i.e., excluding dysfluency) during the past three decades. Data reduction methods for the speech samples included narrow phonetic transcription, prosody-voice coding, and acoustic analyses. Standardized measures were used to cross-classify participants' speech and motor speech status. Compared to the 17.8% prevalence of four types of motor speech disorders reported in a study of 415 participants with idiopathic Speech Delay (SD), 47.7% of the present participants with CND met criteria for one of four motor speech disorders, including Speech Motor Delay (25.1%), Childhood Dysarthria (13.3%), Childhood Apraxia of Speech (4.3%), and concurrent Childhood Dysarthria and Childhood Apraxia of Speech (4.9%). Findings are interpreted to indicate a substantial prevalence of speech disorders, and notably, a substantial prevalence of motor speech disorders in persons with some types of CND. We suggest that diagnostic classification information from standardized motor speech assessment protocols can contribute to research in the pathobiologies of CND. Abbreviations: 16p: 16p11.2 deletion and duplication syndrome; 22q: 22q11.2 deletion syndrome; ASD: Autism Spectrum Disorder; CAS: Childhood Apraxia of Speech; CD: Childhood Dysarthria; CND: Complex Neurodevelopmental Disorder; DS: Down syndrome; FXS: Fragile X syndrome; GAL: Galactosemia; IID: Idiopathic Intellectual Disability; MSD: Motor Speech Disorder; No MSD: No Motor Speech Disorder; NSA: Normal(ized) Speech Acquisition; PEPPER: Programs to Examine Phonetic and Phonologic Evaluation Records; PSD: Persistent Speech Delay; PSE: Persistent Speech Errors; SD: Speech Delay; SDCS: Speech Disorders Classification System; SDCSS: Speech Disorders Classification System Summary; SE: Speech Errors; SMD: Speech Motor Delay; SSD: Speech Sound Disorders; TBI: Traumatic Brain Injury